Made with Love: Tracing Personal and Cultural Resilience in Annie Pootoogook’s Drawings - Lawrence, Emily (2018)
Looking at the drawings of Kinngait-born Inuk artist Annie Pootoogook (1969– 2016), this major research paper foregrounds deep readings of the artist’s work beyond other narratives that have historically eclipsed such analyses of Inuit art. Through examining a series of Pootoogook’s drawings pertaining to matriarchal love and Inuit-specific recurring imagery such as the amauti (mother’s coat), I propose that these works reveal a way of expressing love, doubly marking the artist’s own personal and cultural resilience. Following the groundwork laid by Inuk art historian Heather Igloliorte, I draw on tenets from Inuit Qaujimajatuqangit (living knowledge or that which Inuit have always known to be true) to suggest ways in which Pootoogook uses the medium of drawing to express love for family and culture while simultaneously strengthening relations with both. By placing Pootoogook’s drawings in dialogue with broader Indigenous theory and Inuit-specific epistemology (to the best of my own non-Inuit or qallunaat ability), I hope to suggest new avenues through which more expansive scholarship on Pootoogook’s work can continue to develop.